Pengaruh Country Of Origin Terhadap Purchase Intention Dimediasi oleh Customer Trust: Studi pada Kopi Janji Jiwa di Kota Bandung - Sukmaningrum, Via Ayu; R. Nurafni Rubiyanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Due to an increase in people's purchasing power, competition between local and international coffee chain businesses is getting tougher. The number of stores and the value of sales indicate that there is competition. Kopi Janji Jiwa has the most shops in Indonesia, but its sales value is lower than that of its rivals. This demonstrates that factors like origin country have an impact on sales value. However, customer trust is required because it is insufficient to be considered. Companies that have a good country of origin and customers who trust them can make more people want. The purpose of this study is to ascertain how customer trust in Janji Jiwa Coffee influences purchase intention in relation to country of origin. With a descriptive approach, the quantitative research method was used, using nonprobability sampling technique with purposive sampling type where the number of respondents is 150 respondents. Through the distribution of questionnaires to Bandung residents who knew about, had not purchased, or had ever purchased Kopi Janji Jiwa, data were gathered. Information examination was done utilizing SmartPLS 3.2.9 programming. The findings demonstrated that customer trust has a positive impact on purchase intention, that customer trust has a positive impact on purchase intention, and that country of origin has a positive impact on purchase intention. The discoveries likewise show that nation of beginning emphatically affects purchase intention interceded by client trust in Janji Jiwa Coffee.